Exceptional preservation and the fossil record of tetrapod integument. Issue 1862 (6th September 2017) - Eliason, Chad M.; Hudson, Leah; Watts, Taylor; Garza, Hector; Clarke, Julia A.
Abstract : The fossil record of exceptionally preserved soft tissues in Konservat-Lagerstätten provides rare yet significant insight into past behaviours and ecologies. Such deposits are known to occur in bursts rather than evenly through time, but reasons for this pattern and implications for the origins of novel structures remain unclear. Previous assessments of these records focused on marine environments preserving chemically heterogeneous tissues from across animals. Here, we investigate the preservation of skin and keratinous integumentary structures in land-dwelling vertebrates (tetrapods) through time, and in distinct terrestrial and marine depositional environments. We also evaluate previously proposed biotic and abiotic controls on the distribution of 143 tetrapod Konservat-Lagerstätten from the Permian to the Pleistocene in a multivariate framework. Gap analyses taking into account sampling intensity and distribution indicate that feathers probably evolved close to their first appearance in the fossil record. By contrast, hair and archosaur filaments are weakly sampled (five times less common than feathers), and their origins may significantly pre-date earliest known occurrences in the fossil record. This work suggests that among-integument variation in preservation can bias the reconstructed first origins of integumentary novelties and has implications for predicting where, and in what depositional environments, to expect further discoveries of exquisitely preserved tetrapod integument.